Online Vs In-Class: EFL Students’ Oral Presentation Preferences - Farida Noor Rohmah (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2024)
The objective of this study is to analyze the preferences and experiences of students with regards to in-class oral presentations as opposed to online oral presentations in English class. The participants for this study were 61 students selected purposively, with a concentration on students in their fourth semester at the Faculty of Health Sciences. The data were collected using a questionnaire and a semi-structured interview. The results show that students have a strong preference for online presentations, both in terms of general satisfaction and ease of preparation, indicating the perceived advantages of the online format over traditional in class presentations. The majority of students believe that online presentations improve their communication skills. The findings have important implications for educators and institutions seeking to improve the effectiveness of oral presentation methods.